Evaluating trifluridine + tipiracil hydrochloride in a fixed combination (TAS-102) for the treatment of colorectal cancer. (13th April 2018) - Mulet, N.; Matos, I.; Noguerido, A.; Martini, G.; Élez, M. E.; Argilés, G.; Tabernero, J.
ABSTRACT: Introduction : Despite major progress in treating advanced colorectal cancer (CRC), prognosis in this population after progression on standard treatment remains dismal and the development of new drugs represents an unmet need. Historically, fluoropyrimidines have played a major role in the treatment of metastatic CRC. TAS-102, a novel combination of trifluridine and tipiracil hydrochloride, has demonstrated improvement in overall survival in the refractory CRC setting, with a safe toxicity profile. Areas covered : A literature review of published clinical studies was performed. Herein, the authors review the pharmacological and clinical data of TAS-102 when used in metastatic CRC, both as a single agent as well as in novel combinations under investigation. Expert opinion : The addition of TAS-102 to the therapeutic armamentarium of metastatic CRC is an encouraging breakthrough considering the demonstrated survival benefit and favorable tolerability profile. Combinations with other agents are under clinical investigation in different settings in an attempt to widen its use. To optimize treatment in today's era of molecular oncology, efforts should be focused on understanding primary and secondary resistance mechanisms, along with the identification of potential biomarkers of response.